INOVASI MEDIA PENILAIAN BAHASA ARAB MENGGUNAKAN POWER POINT - Aisyatul Hanun; Amirul Mukminin; Shofwatul Widad (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2021)
The process stages of innovation evaluation using power points is begun by mudarris’ complaint about an inefficient assessment process because it uses an inappropriate instrument, until in 2018 a grading of assessment questions was formed. By continuing to be pursued, evaluated and developed, now the design of power point applications that can be used as an instrument in the implementation of assessments in Arabic learning of female students with implementation practices as follows; students listen to istima’ audio, then conclude about what they can understand from the audio they have listened, then students write words that they can remember from what they have listened before, read the qiro'ah texts that have been available on the power point, and finally answer some questions about qawaid. The results of this innovation design can be declared worthy of being a good instrument because it meets the criteria. In addition, the results of this design were also very successful in covering the implementation of the assessment when assessing the skills of the four language skills (maharah), and also the ability of understanding qawaid that students have.